2018
DOI: 10.3390/cancers10080264
|View full text |Cite
|
Sign up to set email alerts
|

The SUMO System and TGFβ Signaling Interplay in Regulation of Epithelial-Mesenchymal Transition: Implications for Cancer Progression

Abstract: Protein post-translational modification by the small ubiquitin-like modifier (SUMO), or SUMOylation, can regulate the stability, subcellular localization or interactome of a protein substrate with key consequences for cellular processes including the Epithelial-Mesenchymal Transition (EMT). The secreted protein Transforming Growth Factor beta (TGFβ) is a potent inducer of EMT in development and homeostasis. Importantly, the ability of TGFβ to induce EMT has been implicated in promoting cancer invasion and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 116 publications
2
18
0
Order By: Relevance
“…The EMT and the TGF-β pathways are one of the most important mechanisms underlying the metastatic ability of cancer cells (56,57). We have previously shown the importance of the EMT in breast cancer (58) and here, we show that GO term analysis based on the DE miRNAs showed a signi cant association with the biological process "positive regulation of mesenchymal cell proliferation" (GO:0002053).…”
Section: Discussionsupporting
confidence: 60%
“…The EMT and the TGF-β pathways are one of the most important mechanisms underlying the metastatic ability of cancer cells (56,57). We have previously shown the importance of the EMT in breast cancer (58) and here, we show that GO term analysis based on the DE miRNAs showed a signi cant association with the biological process "positive regulation of mesenchymal cell proliferation" (GO:0002053).…”
Section: Discussionsupporting
confidence: 60%
“…In this study, we found that SP1 could significantly increase the levels of SMAD7 mRNA and proteins and inhibit the expression of TGF-βRI, thus reducing the phosphorylation levels of downstream SMAD2 and SMAD3 of TGF-βRI. Meanwhile, our study found that SP1 could inhibit the mRNA and protein expression of proliferation, apoptosis, migration, and invasion-related genes SOX4, ZEB2, MMP9, Snail, and Slug, which are all downstream molecules of TGF-β/SMAD signaling pathway [17,18]. SOX4, a member of the C-subfamily of SOX transcription factors, promotes tumorigenesis by enabling cancer cells to survive, migrate, and invade [19]; MMP9, a member of the matrix metalloproteinase (MMP) family, plays an important role in tumor migration and invasion, angiogenesis, and apoptosis [20]; the transcription factors Snail and Slug are important molecules in the EMT process, which can promote tumor invasion and metastasis, and facilitate cell survival by regulating the cell cycle and apoptosis [21,22].…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, PI3K promotes the activation of PAK1, which phosphorylates Snail at Ser246, promoting its nuclear translocation and the control of the expression of EMT-related genes [ 78 ]. Additionally, SUMOylation of Snail at Lys234 stabilizes and promotes its translocation to the nucleus, allowing its interaction with c-Jun to regulate gene expression [ 79 ]. Snail phosphorylation at Ser11 by PKA and Ser92 by CK2 regulates the transcriptional repression of CDH1 and CLDN1 through the recruitment of the transcriptional repressor mSin3A and histone deacetylases (HDACs), responsible for decreasing the acetylation at H3 and H4 of CDH1 promoter [ 80 , 81 ].…”
Section: Emt-related Transcription Factorsmentioning
confidence: 99%
“…Slug is phosphorylated by ERK1/2 at Ser100 to promote its nuclear localization and at Ser87 to regulate its transcriptional activity [ 88 ]. Also, the SUMOylation of Slug at Lys192 increases its stability and promotes its ability to suppress the expression of E-cadherin [ 79 ]. Slug is degraded through the p21–p53–Mdm2 complex via ubiquitination [ 86 , 89 , 90 ] and through phosphorylation by GSK3β at Ser92 via proteasome degradation [ 88 ].…”
Section: Emt-related Transcription Factorsmentioning
confidence: 99%